Contemporary outcomes of the concomitant CryoMaze procedure. (28th February 2019) - Kakuta, Takashi; Fukushima, Satsuki; Minami, Kimito; Shimahara, Yusuke; Yamasaki, Takuma; Matsumoto, Yorihiko; Yamashita, Kizuku; Kawamoto, Naonori; Tadokoro, Naoki; Kabata, Daijiro; Kobayashi, Junjiro; Fujita, Tomoyuki
Abstract: OBJECTIVES: As an institutional strategy, the CryoMaze procedure has been established for treating atrial fibrillation (AF) since 2001. In this study, we aimed to analyse the contemporary outcomes of the CryoMaze procedure and to examine the predictive factors of successful sinus rhythm conversion. METHODS: Between January 2009 and March 2018, we performed 352 CryoMaze procedures. The contemporary outcomes of the CryoMaze procedure concomitant with other cardiac procedures were analysed by the Kaplan–Meier method. The logistic regression model was used to predict risk factors for recurrent AF. RESULTS: There were no 30-day or in-hospital deaths and all of the patients were discharged. The 1- and 5-year survival rates were 99.0% and 94.6%, respectively. The rates of freedom from permanent pacemaker implantation and cerebrovascular accidents were 92.6% at 1 year and 86.9% at 5 years, and 99.1% at 1 year and 97.9% at 5 years, respectively. The rates of freedom from recurrent permanent AF were 91.9% at 1 year and 86.1% at 5 years. The multivariable analysis showed that the independent predictive factors for recurrent permanent AF included an F-wave grade in lead V1 ( P < 0.001), the preoperative duration of persistent AF ( P = 0.031), a non-mitral procedure ( P = 0.019) and a preoperative tricuspid regurgitation grade ( P = 0.034). CONCLUSIONS: Preoperative voltage of the F wave in V1 lead is strongly associated with the sinus rhythm restoration after the CryoMaze procedure.